The impact of disasters on contraception in OECD member countries: a scoping review. (3rd September 2021) - Freed, Benjamin; Hillman, Sarah; Shantikumar, Saran; Bick, Debra; Dale, Jeremy; Gauly, Julia
Abstract: Objectives: Review evidence is lacking about how contraception is affected by severe social disruption, such as that caused by the COVID-19 pandemic. The purpose of this scoping review was to explore the impact of natural and man-made disasters on contraception in OECD member countries. Methods: Manual searches and systematic searches in six electronic databases were conducted with no language restrictions. All articles were screened by at least two researchers. The data were analysed thematically. Results: 108 articles were included. Most focussed on the Zika virus outbreak ( n  = 50) and the COVID-19 pandemic ( n  = 28). Four key themes were identified: importance of contraception during disasters, impact of disasters on contraceptive behaviour, barriers to contraception during disasters and ways of improving use of contraception during disasters. Despite efforts to increase access to contraception including by transforming ways of delivery, barriers to use meant that unmet need persisted. Conclusions: To prevent adverse health outcomes and reduce health costs as a result of failure to have access to contraception during disasters, there is a need to intensify efforts to remove barriers to use. This should include increasing access and information on methods of contraception and their side effects (e.g., menstrual suppression) and making contraception freely available.